Fuzzy Games for Simulation of Uncertainty in Decision Making by Syrian Wastewater Treatment Plant Projects - عمران جمال (Latakia University Journal -Engineering Sciences Series, 2021)
Wastewater treatment is one of the important elements for achieving sustainable development due to its close association with its economic, social and environmental concepts. This are achieved through the selection of the optimal treatment system, but most treatment systems in Syria did not succeed because these systems were transferred from other countries without testing the extent of their suitability to them. In addition, that studies conducted on treatment systems were based on other conditions and data, which makes it necessary to re-adjust them to suit local conditions. It is shown that this methodical instrumentation allows adequate formulation of the real situation. If a strategy (e.g., the choice of treatment plant type) is to be optimal, it must satisfy the strategy characterizing attributes of the solution’s performance (parameters, features, etc.). The score evaluation is not subordinate to the crisp logic, but is a fuzzy term. To understand this relation more closely, the influence parameters on the system that characterize the quality attributes can be divided into two main groups, internal and external parameters of the system. Between these two groups, the conflict can be handled as a game. Two peculiarities can be mentioned here: 1- The decision is strategic, 2- The information content is low, with information gathering increasing as the decision.